2013
DOI: 10.1111/1574-6968.12129
|View full text |Cite
|
Sign up to set email alerts
|

Surface hydrophobicity and roughness influences the morphology and biochemistry of streptomycetes during attached growth and differentiation

Abstract: Streptomycetes, soil-dwelling mycelial bacteria, can colonise surface of organic soil debris and soil particles. We analysed the effects of two different inert surfaces, glass and zirconia/silica, on the growth and antibiotic production in Streptomyces granaticolor. The surfaces used were in the form of microbeads and were surrounded by liquid growth media. Following the production of the antibiotic granaticin, more biomass was formed as well as a greater amount of antibiotic per milligram of protein on the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Statistical correlation tests were not performed with the experimental data from the measurements of roughness, wettability and adhesion of microorganisms because the dentine samples used in the different sets of experiments were not the same, although they were prepared identically. The increase in roughness Irrigants, dentine and microorganism's adhesion Tartari et al and wettability is shown to increase the adhesion of microorganisms on surfaces (Mei et al 2011, Tang et al 2011, Petrackova et al 2013. However, the effects of roughness and wettability on the adhesion of the tested microorganisms could not be established by this study, as previously described (Burgers et al 2010, do Nascimento et al 2013.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Statistical correlation tests were not performed with the experimental data from the measurements of roughness, wettability and adhesion of microorganisms because the dentine samples used in the different sets of experiments were not the same, although they were prepared identically. The increase in roughness Irrigants, dentine and microorganism's adhesion Tartari et al and wettability is shown to increase the adhesion of microorganisms on surfaces (Mei et al 2011, Tang et al 2011, Petrackova et al 2013. However, the effects of roughness and wettability on the adhesion of the tested microorganisms could not be established by this study, as previously described (Burgers et al 2010, do Nascimento et al 2013.…”
Section: Discussionmentioning
confidence: 49%
“…, Petrackova et al . ). However, the effects of roughness and wettability on the adhesion of the tested microorganisms could not be established by this study, as previously described (Burgers et al .…”
Section: Discussionmentioning
confidence: 97%
“…To establish conclusions on the role of the modification further parallel and duplicated experiments are necessary and will be carried out. In many cases biofilm development of wastewater and soil isolates was shown to be increased on hydrophilic surfaces [49][50][51], but, in contrast, unmodified and to a lesser extent more hydrophobic surfaces were preferred by the dominant bacterial strains in this study resulting in thicker biofilms. In the work by Petrackova et al [51] Streptomycetes were also found to colonize hydrophobic surfaces but this resulted in an altered protein expression.…”
Section: Accepted M Manuscriptmentioning
confidence: 57%
“…In many cases biofilm development of wastewater and soil isolates was shown to be increased on hydrophilic surfaces [49][50][51], but, in contrast, unmodified and to a lesser extent more hydrophobic surfaces were preferred by the dominant bacterial strains in this study resulting in thicker biofilms. In the work by Petrackova et al [51] Streptomycetes were also found to colonize hydrophobic surfaces but this resulted in an altered protein expression. A similar phenomenon might also play a role in the selectivity of the surfaces used in this work for the specific group of γ-Proteobacteria, which were initially inoculated in equal amounts by using the same sludge.…”
Section: Accepted M Manuscriptmentioning
confidence: 57%
“…The surface roughness seems to be a characteristic feature of biofilm indwellers. It has been reported that cells with rough appearance are more hydrophobic and these phenotypes exhibit strong surface colonization and adhesion abilities [22]. Kaiser [23] described those bacteria which showed elongated cells, have the competitive advantage of the colony edge.…”
Section: Discussionmentioning
confidence: 99%